Patterns of Stakeholder Relationships in the Implementation of the Tomira Partnership Program in Kulon Progo - Wijaya, Riko (Department of Government Studies, Universitas Syiah Kuala, 2024)
TOMIRA stands for People's Owned Stores, which emerged as a reaction to the widespread growth of modern networked or franchised stores in the community, especially in Kulon Progo Regency. The development of modern network stores or franchises is considered a threat to the long-term existence of traditional markets, which in this case include cooperatives and micro, small and medium enterprises (MSMEs). TOMIRA is a partnership program between cooperatives, MSMEs, and large networked modern shop companies supported by the Kulon Progo Regency government in an effort to provide solutions for the sustainability of cooperatives and MSMEs in society. However, the TOMIRA partnership program still has various deficiencies, especially in terms of the roles and relationship patterns of the stakeholders involved. Therefore, the purpose of this study is to examine the pattern of relationships that occur between stakeholders involved in the implementation of the TOMIRA partnership program so that this program is expected to have a high success rate and be beneficial to various parties in the future.